As Greek as it gets: British attempts to recreate the Parthenon - Fehlmann, Marc (Routledge Journals, Taylor & Francis Ltd, 2007)
The arrival of the Elgin Marbles in Britain and several ambitious attempts to reconstruct the Parthenon in London, Cambridge and elsewhere fostered its general reputation as 'a building from which derived all that is good'. While it is well known that the high esteem held for the Parthenon after the defeat of Bonaparte was predicated by a change in taste and by associating this monument with the defeat of the Persians by the Greeks in 479 BC, another crucial issue has as yet been overlooked: the self-interest of those attempting to recreate the Parthenon. By linking their own present with an alien, even fictitious, past, they wished to associate themselves with an aura of greatness that would suggest their own heroic power. Putting themselves on the same level as Pericles, Pheidlas, Iktinos and Kallikrates, they could argue for their own cultural superiority while hoping for kleos aphthiton-fame and glory that outlast death. No other monument from the ancient world could, at the time, have offered a more suitable basis for such approbation. The article focuses on the British reception of the Parthenon in the early nineteenth century. It introduces new evidence as to how and why, after the Napoleonic Wars, the British epitomized the Periclean monument as the pinnacle of human accomplishment. It argues that the monument was reintegrated into the Western art canon by replicating its sculpture through plaster casts and by substituting historic facts for fiction. As the unique quality of the Parthenon's architecture was not known and published prior to 1838 and not introduced to a British audience before 1851, the Parthenon could only have gained its importance and fame because of the physical presence of the Elgin Marbles. Hence, I will make clear that the sculpture was a pivotal element in rendering the Parthenon a canonical monument.
37th Annual Meeting of the American-Society-for-Eighteenth-Century-Studies -- MAR 31, 2006 -- Montreal, CANADA
Keywords: Parthenon; historical reenactment; sculpture; Elgin Marbles; nineteenth-century Britain; classical antiquity